Analysis of mortality due to traffic accidents at Hospital de Clínicas - Cepellini, Raúl; Henderson, Eduardo; Müller, Augusto; Bañales, Cecilia (Cirugía del Uruguay, 1997)
A descriptive study is carried out on 113 cases of trauma due to road accidents admitted to the Emergency Department at the Hospital de Clínicas between May 1995 and September 1996. Authors analyse epidemiology, paraclinical tests, treatment, and specially point out mortality, confirming the importance ot the use ot helmet in the case of motorcyc/ists and of safety belts in the case of motorists. The direct relationship between speed and mortality is discussed.